Toxicity Test of Flavonoid Compounds from Ethyl Acetate Extract of Malacca Leaves with Brine Shrimp Lethality Test - Zakwan, Muhammad; Sutriana, Amalia; Nurliana, Nurliana; Asmilia, Nuzul; Ammar, Muhammad; Novianti, Arindita Niatazya (Universitas Airlangga, 2023)
Flavonoids are a group of polyphenolic compounds produced in plants as secondary metabolites. Flavonoids have favorable biochemical effects on multiple diseases and other bioactivities. This study aimed to isolate the active compounds contained in malacca (Phyllanthus emblica) leaves and analyze toxic properties using the Brine Shrimp Lethality Test (BSLT) method in Artemia salina leach shrimp larvae. This study used malacca leaf powder with ethyl acetate solvent then macerated. Ethyl acetate extract was concentrated and fractionated, then toxicity tests were carried out. Extracts from the evaporation results were further fractionated using solvent petroleum ether, diethyl ether, and ethyl acetate. Then the ethyl acetate fraction was hydrolyzed using reflagged with 7% sulfuric acid for two hours, then the filtrate was extracted with ethanol solvent. The obtained fraction washed with aquades and dried using a vacuum desiccator. The toxicity test results showed that the flavonoid compound of malacca leaves was not toxic with a value of LC50 > 1000 ppm, an increase in the concentration of the extract was followed by an increase in the average mortality of larvae.